Effect of Stirring Speed and Solid to Solvent Ratio on Fucoidan Yield from Sargassum sp. - Naili Uswatun Hasah; Dewi Purnama Wati; Sugiono Sugiono (Journal of Experimental Life Science)
Brown alga Sargassum sp. has bioactive alginate and fucoidan, which have the potential for raw materials in the biorefinery industry with core processing of fucoidan and alginate extraction. Fucoidan is a polysaccharide found in the cell wall matrix of brown alga Sargassum sp. and functions as an anti-cancer, immunomodulatory, and anti-inflammatory. This research aims to determine the effect of stirring speed and solid-to-solvent ratio on fucoidan yield. A 2K factorial experimental design was used to determine the effect of process conditions, stirring speed, and solid-to-solvent ratio on fucoidan yield. Analysis of yield response data and model accuracy was carried out by regression analysis using the Design Expert program. The results showed that the stirring speed and solid-to-solvent ratio affected the yield of fucoidan. The highest fucoidan yield of 3.77% occurred at a stirring speed of 750 rpm and a solid-to-solvent ratio of 1:20 (g.mL-1). The first-order experimental model is quadratic. The model test shows that the curvature is significant at the confidence level α = 0.05.